Replacement of the Aortic Root and Ascending Aorta for Acute Aortic Dissection in a Patient with Liver Cirrhosis (Child-Pugh Class B) and Hepatic Cell Carcinoma - Saito, Yosuke; Murakami, Mikiko; Asai, Tomohiro; Yamaguchi, Hiroki; Nakamura, Koki (Japanese Journal of Cardiovascular Surgery, 2007)
A 62-year-old man was referred to us because of acute aortic dissection (Stanford type A). He had had liver cirrhosis (Child-Pugh class B) and hepatic cell carcinoma in the left lateral lobe, which had been resected 3 years ago. On admission he was drowsy and was in shock. CT showed dissection from the ascending aorta to the abdominal aorta. Echocardiography revealed severe aortic regurgitation. An emergency operation was indicated although it was a very high risk procedure. Under cardiopulmonary bypass with moderate hypothermia, the aortic root was replaced with a Freestyle valve (23mm). Then the ascending aorta was replaced with a woven Dacron graft (28mm) under cardiac arrest and isolated cerebral perfusion. Postoperatively, he had cardiac tamponade and cerebral infarction (perhaps due to the preoperative events). However, he was successfully discharged on the 34th postoperative day.